Fluorine‐Free Slippery Liquid‐Infused Porous Surfaces Prepared Using Hierarchically Porous Aluminum. Issue 13 (13th July 2020) - Inoue, Tomohiro; Koyama, Akira; Kowalski, Damian; Zhu, Chunyu; Aoki, Yoshitaka; Habazaki, Hiroki
Abstract : Slippery Surfaces In article number 1900836 by Tomohiro Inoue, Hiroki Habazaki and co‐workers, fluorine‐free slippery liquid‐infused porous surface (SLIPS) is prepared using hierarchically porous aluminum substrate and silicone lubricant. The F‐free SLIPS is more environmentally acceptable compared with the F‐containing SLIPS and exhibits highly reduced ice adhesion and excellent corrosion resistance in NaCl solution rather than the corresponding superhydrophobic surface.